Ultrasonic-assisted extraction of polysaccharides from Albizia julibrissin Durazz. leaf and pod: process optimization, physicochemical properties and anticomplementary activity - Yuanqi Duan; Yuxin Jiang; Jiayu Gu; Chenxi Sun; Boshi Sun; Yue Xu; Long Jin; Mei Jin; Mei Jin; Jinfeng Sun; Wei Zhou; Zhengyu Hu; et al. (Frontiers in Sustainable Food Systems)
This study employed ultrasound-assisted extraction to obtain polysaccharides from Albizia julibrissin Durazz. leaf and pod agricultural by-products, with subsequent process optimization. A comparative analysis was then conducted on the physicochemical properties and anticomplementary activity of the isolated polysaccharides derived from two parts. The investigation identified different extraction conditions for leaf and pod, leaf demonstrated maximum polysaccharide yield (1.07 ± 0.20%) at 70°C, 40 mL/g, 50 min and 249 W, contrasting with pod which achieved 8.32 ± 0.27% yield at 70°C, 28 mL/g, 40 min and 201 W. Besides, physicochemical characterization demonstrated distinct molecular weights between leaf (AJLP) and pod (AJPP) polysaccharides (62.55–232.30 kDa) despite shared functional groups. Both polysaccharides contained mannose, rhamnose, glucuronic acid, galacturonic acid, glucose, galactose, xylose, and arabinose in varying ratios, while displaying divergent microstructures and excellent thermal stability. In vitro, leaf (AJLP) and pod (AJPP) polysaccharides exhibited potent anticomplementary activity in alternative and classical pathways, respectively. This study established a foundation for developing and utilizing polysaccharide resources from A. julibrissin agro-byproducts, while providing a theoretical basis for their application in complement system overactivation.